Overconfidence in Investment Decisions: An Experimental Approach - Dennis Dittrich; Werner Güth; Boris Maciejovsky (Center for Economic Studies and ifo Institute (CESifo), 2001)
We experimentally test overconfidence in investment decisions by offering participants the possibility to substitute their own for alternative investment choices. Overall, 149 subjects participated in two experiments, one with just one risky asset, the other with two risky assets. Overconfidence increases (i) with the absolute deviation from optimal choices, (ii) with task complexity, and (iii) decreases with uncertainty as indicated by the difference between willingness to pay and to accept.
Keywords: 330; risky decision making; behavioral finance; portfolio choice; experimental economics